The impact of working capital management on firm’s profitability: evidence from Malaysian listed manufacturing firms - Sin, Huei Ng; Ye, Chen; Tze, San Ong; Boon, Heng Teh (EconJournals, 2017)
This study investigates the relationship between working capital management and firm’s profitability of Malaysian listed manufacturing firms. It aims to examine the impact of working capital management from the aspects of aggressive working capital policy and efficiency of working capital management. Data is obtained from the annual reports of 122 firms listed in the industrial products sector of Bursa Malaysia Main board for the 6 year period from 2007 to 2012 to determine the relationships between the variables of working capital management and firm’s gross operating income (GOI). The results indicate that GOI is negatively related to the degree of aggressiveness of investment policies but positively related with the degree of aggressiveness of financing policies. Moreover, as a comprehensive measure of the efficiency of working capital management, the study finds cash conversion cycle is positively related to GOI. It shows that an increase in inventory conversion period is positively related to firms’ profitability. Likewise, firms can increase profitability by reducing the period of collecting account receivables.